CLIC1 and CLIC4 Ion Channel Deficiency Confers Increased Sensitivity to Tumour Treating Fields and Improved Survival in Paediatric Glioblastoma. (1st October 2022) - Griffin, Michaela; Basu, Surajit; Khan, Raheela; Smith, Stuart
Abstract: AIMS: (1) To determine if specific and unique chloride intracellular channel (CLIC) expression patterns exist in paediatric glioblastoma. (2) To assess if these expression patterns can be exploited as a treatment strategy. (3) To assess the combination of ion channel manipulation with Tumour Treating Fields (TTFields). METHOD: CLIC channel expression patterns were identified via multivariate analysis of in-house and publicly available data sets and RNA sequencing of in-house patient tumour samples. siRNA depletion or inhibition via IAA94 of CLIC1 and CLIC4 was assessed using cell cycle, clonogenic, migration and proliferation assays, alone and in combination with TTFields. Whole transcriptome gene expression analysis (Human Clairom™ Array) of pGBM cells treated with TTFields was carried out. RESULTS: Clinical correlation determined that CLIC4 and CLIC1 deficiency was associated with increased overall survival, with siRNA depletion propagating a reduction in the proliferation, migration and invasion of pHGG cell lines associated with cell cycle arrest. Furthermore, CLIC1 and CLIC4 deficiency exacerbated the killing capacity of TTFields, reducing clonogenic and proliferative capabilities. Whole transcriptome gene expression analysis of paediatric GBM cell lines treated with TTFields and found that cells treated with TTfields exhibited a down-regulation in CLIC1 and CLIC4 compared to untreated cells. CONCLUSION: These data provide rationale that genetic, electrical, and pharmacological manipulation of ion channels can reduce the capacity of childhood brain tumours to proliferate and invade. CLIC channels may be a suitable target for combination therapy to enhance the treatment efficacy of TTfields and help bring this non-invasive therapy to paediatric patients.